2003
DOI: 10.1152/ajpheart.01025.2002
|View full text |Cite
|
Sign up to set email alerts
|

Novel complexes of guanylate cyclase with heat shock protein 90 and nitric oxide synthase

Abstract: . Novel complexes of guanylate cyclase with heat shock protein 90 and nitric oxide synthase. Am J Physiol Heart Circ Physiol 285: H669-H678, 2003. First published April 3, 2003 10.1152/ajpheart.01025.2002 is an important downstream intracellular target of nitric oxide (NO) that is produced by endothelial NO synthase (eNOS) and inducible NO synthase (iNOS). In this study, we demonstrate that sGC exists in a complex with eNOS and heat shock protein 90 (HSP90) in aortic endothelial cells. In addition, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
2
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 30 publications
8
120
2
5
Order By: Relevance
“…Caveolae are therefore regulatory platforms for the cascade of events resulting in NO production. Although the natural receptor for NO, sGC has been detected in association with the plasma membrane (Zabel et al, 2002;Venema et al, 2003), and sGC is translocated to caveolar domains to be sensitized by NO (Zabel et al, 2002); the interaction with caveolin-1 and the role of this association with the plasma membrane in blood vessel relaxation are unknown. We observed that the relaxation induced by the sGC activator YC-1 is impaired in the presence of methyl-␤-cyclodextrin in rat aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolae are therefore regulatory platforms for the cascade of events resulting in NO production. Although the natural receptor for NO, sGC has been detected in association with the plasma membrane (Zabel et al, 2002;Venema et al, 2003), and sGC is translocated to caveolar domains to be sensitized by NO (Zabel et al, 2002); the interaction with caveolin-1 and the role of this association with the plasma membrane in blood vessel relaxation are unknown. We observed that the relaxation induced by the sGC activator YC-1 is impaired in the presence of methyl-␤-cyclodextrin in rat aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of ␤ 1 [204 -408] appears to have a greater impact on the stability of ␣ 1 , as indicated by our findings that ␣ 1 protein was more readily down-regulated than ␤ 1 protein and that ␤ 1 [204 -408] was readily detected in ␤ 1 but not in ␣ 1 coimmunoprecipitates. These phenomena might relate to the fact that only ␤ 1 but not ␣ 1 interacts with and is stabilized by heat shock protein hsp90 (6). It is tempting to speculate that expression of alternatively spliced variants or isoforms of the ␤ subunit exposing modified N-or C-terminal portions but retaining the dimerization region may contribute to the fine tuning of cellular cyclase activity through targeted degradation of the resultant complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms implicated were suppression of osteopontin, TGF-␤, and intrarenal C-reactive protein expression together with higher eNOS expression (70). However, the beneficial effect of pravastatin in very high doses (20 mg/kg) was not observed in rats that received lower doses (5 mg/kg).…”
Section: Invited Reviewmentioning
confidence: 98%